Characteristics of Children with Colorectal Polyps. Experience in Northern Peru - Ormeño-Julca, Alexis José (2025)
Background: Colorectal polyps are tumors that protrude into the lumen of the gastrointestinal tract and, in the pediatric population, are most commonly located in the rectosigmoid region, being predominantly benign. Objective: To describe the epidemiological, clinical, endoscopic, and histological characteristics of children with colorectal polyps treated in Chiclayo, Peru. Materials and Methods: Observational, descriptive, retrospective, and cross-sectional study conducted between July 2013 and February 2022, including patients with an endoscopic diagnosis of colorectal polyps. Results: A total of 109 patients were included (median age: 6 years; slight female predominance). All patients presented with rectal bleeding, and 40% exhibited polyp prolapse through the anus. A single polyp was identified in 70.6% of cases, while 3.7% had polyposis. A total of 178 polyps were removed, 75.8% of which were located in the rectum. Histologically, 80.3% were juvenile polyps. Conclusion: In children, colorectal polyps most frequently present with rectal bleeding, with juvenile and solitary rectal polyps being the most common findings